Exportable Central America: Contributions to the historiography of Central American Modern Art - Vindas Solano, Sofía (2023)
The following article studies the historiography of Central American and Latin American art, to establish some trends in how they have been analyzed and what contributions these fields of knowledge have made to the understanding of regional visual arts and Central American cultural history. Additionally, in contrast to this state of the matter, the article establishes some contributions made by the doctoral thesis to the knowledge of this historiography, the thesis is: “Making Central America exportable: activation of international art circuits and its impact on the consolidation of modern art museums and collections in Guatemala and Costa Rica, 1950-1996”. Two specific contributions made by the thesis are analyzed: on the one hand, how the research conclusively evidences those certain Central American artists that vigorously participated in international artistic networks in the second half of the 20th century. The research reconstructs this, through a mapping of the events in which these artists participated. Additionally, another contribution is how the research problematizes what has been said about the characteristics of Central American modern art through an analysis of the collections of three regional museums.